A finança encontra o bloco no poder: ensaios sobre transnacionalização do capital e dominação política de classe - Andrade, Patrick Rodrigues (2019)
The thesis is composed of three essays dealing with the relations between economic determinations and political determinations in studies on capitalism and class relations. The first essay revisits criticisms of Louis Althusser's formulations about the place of social classes in his work and the criticisms of the “theoricist” “politicist” character of Poulantzas work. After offering some answers to these criticisms that are already present in the works of the two authors, it is proposed, as a subsidy for the structural analysis of class relations in concrete social formations, the development and use of two notions formulated originally by Nicos Poulantzas: “pertinent effects” and “index of effectiveness”. Our expectation is that such notions, if worked as medium-range analytical operators, can help address contradictory processes of determination and overdetermination of classes, especially the capitalist class in concrete social formations. The second essay discusses the relation between fully fetishized forms of capital and fictitious capital. Since, introducing the category of interest-bearing capital, Marx asserts that this is the most fetishized form of capital, this opens the interpretation that all forms assumed by capital have fetishist determinations. The essay develops the idea that it is not only possible for interest bearing capital to reproduce itself (in given situations) without the necessary exploitation of the labour-power, but also that its determinations produce politically relevant economic effects for the analysis of class relations, in particular as regards the power bloc. The third essay discusses the necessary distinction between fractions of capital and fractionations of the capitalist class. The specific objectives are: (i) to criticize a recurring tendency in Marxist analyzes to “overpoliticize” processes determined at the economic level and to expose why the fractions of capital should be read as underdetermined at the economic level; (ii) to expose the possibility of specific fractionations of the capitalist class that are not limited to economic determinations, but which are related to contradictions overdetermined by the relation between structures and practices, especially as effects that the relation between political class practices and state policies can provoke